Scientific writing 3.0 a reader and writer's guide - Lebrun, Jean-Luc (World Scientific, 2021)
"The third edition of this book aims to equip both young and experienced researchers with all the tools and strategy they will need for their papers to not just be accepted, but stand out in the crowded field of academic publishing. It seeks to question and deconstruct the legacy of existing science writing, replacing or supporting historically existing practices with principle- and evidence-driven styles of effective writing. It encourages a reader-centric approach to writing, satisfying reader-scientists at large, but also the paper's most powerful readers, the reviewer and editor. Going beyond the baseline of well-structured scientific writing, this book leverages an understanding of human physiological limitations (memory, attention, time) to help the author craft a document that is optimized for readability. Through real and fictional examples, hands-on exercises, and entertaining stories, this book breaks down the critical parts of a typical scientific paper (Title, Abstract, Introduction, Visuals, Structure, and Conclusions). It shows at great depth how to achieve the essential qualities required in scientific writing, namely being clear, concise, convincing, fluid, interesting, and organized. To enable the writer to assess whether these parts are well written from a reader's perspective, the book also offers practical metrics in the form of six checklists, and even an original Java application to assist in the evaluation"--